Fulminant Vaccine-Induced Immune Thrombotic Thrombocytopenia after ChAdOx1 nCoV-19 (AZD1222) Vaccine Administration in a Woman with Obesity: A Case Report - Yian-Lin Chou; Wei-Sheng Ling; Yih-Hwa Chiou (Acta Neurologica Taiwanica)
Vaccine-induced immune thrombotic thrombocytopenia (VITT), also known as thrombosis with thrombocytopenia syndrome, is a rare complication of ChAdOx1 nCoV-19 (AZD1222) vaccine administration. The overall incidence of VITT worldwide is one case per 100 000 exposures. Because of the high mortality rate from VITT, thorough monitoring is crucial to predict the risk of occurrence. The underlying risk factors for VITT are not fully understood. Potential risk factors include sex (female) and young age (<50 years), but further research must be conducted to confirm these assumptions. We report the case of a woman with obesity, which is a risk factor for deep vein thrombosis in the legs and for pulmonary embolism, who experienced fulminant VITT after AZD1222 vaccine administration.